The power of active choice: Field experimental evidence on repeated contribution decisions to a carbon offsetting program - Martin Kesternich; Daniel Römer; Florens Flues (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We study the effect of a subtle change in the choice architecture on offsetting behavior. In a large-scale field experiment, we examine repeated voluntary contributions to a carbon offsetting program during the online purchase of long-distance bus tickets. In the control group, travelers had the option to offset their carbon emissions resulting from their bus trip, but they could also simply ignore the offer. In the treatment group, travelers were forced to actively choose whether to offset their carbon emissions or not. This "active choice" requirement immediately increased participation in the offsetting program by almost 50%. Investigating returning customers, we find that this treatment remains effective over time. We report evidence that some customers tend to keep avoiding active contribution decisions in subsequent booking decisions.
urn:nbn:de:bsz:180-madoc-418341
Keywords: H41; C93; D03; L92; 330; voluntary carbon offsets; randomized field experiment; default setting; choice architecture